Comprehensive Microbiome and Metabolome Analyses Reveal the Medicinal Components of Paeonia lactiflora - Liping Yang; Mengdi Zhou; Mengting Zu; Jiajia Zuo; Yingdan Yuan (Plants, 2023)
Paeonia lactiflora Pall. is not only a traditional ornamental plant, but also an important medicinal plant. Currently, some P. lactiflora cultivars are used for ornamental purposes, but their potential medicinal value is ignored. To explore the medicinal potential of the ornamental varieties, the medicinal cultivar ‘Hangbaishao’ (HS) and the ornamental cultivar ‘Zifengyu’ (ZFY) were selected, and microbiome and metabolome analyses were performed to compare the composition of the endophytes and metabolites in the roots. The diversity and abundance of bacteria were not significantly different between HS and ZFY; however, the diversity and abundance of endophytic fungi in the ornamental cultivar ZFY were much higher than those in the medicinal cultivar HS. The flavonoids and phenolic acid contents of the ornamental cultivar ZFY were significantly higher than those of the medicinal cultivar HS, indicating that ZFY has medicinal value. The differences in root endophytes between HS and ZFY may lead to differences in phenolic acids and flavonoids. To explore the relationship between endophytes and the accumulation of phenolic acids and flavonoids, a joint analyses of the microbiome and metabolome were performed. The key bacterium, Ruminococcaceae bacterium GD7, led to the accumulation of phenolic acids and flavonoids in the ZFY. This study contributes to future research on the potential medicinal value of ornamental P. lactiflora and provides a new approach for realizing the ‘dual use of medicine and appreciation’ of P. lactiflora.